Оцінка успішності інтродукції ароматичних рослин родини Lamiaceae Lindl. в умовах Полісся України - Kotyuk, L.А.; Rakhmetov, D.B.; Pіnkіna, T.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to evaluate the efficiency of introduction of non-extensively cultivated annual and perennial aromatic plants of the Lamiaceae Lindl. family species and to determine their cultivation perspectives in Ukrainian Polissya. Material and methods. 17 non-traditional annual and perennial Lamiaceae aromatic plants have been studied during 2008–2016 after their introduction in Botanical Garden of Zhytomyr Agroecological University. Laboratory, field and introductory methods have been used to examine the following properties: plant’s general state, peculiarities of seed and vegetative propagation, their winter-, frost-, drought-resistance alongside of disease and pest resistance. Results. Among the cultivated aromatic plants from the Lamiaceae family 3 annual and 8 perennial species which accounts for 67.4 % of the total studied material proved extremely perspective and highly resistant. Under conditions of Ukrainian Polissya they demonstrated adequate growth and development performance, preserving innate life form, fruit bearing ability, resistance to frosts, droughts, pathogenic organisms. Conclusions. Іntroduced plants Dracocephalum moldavica L., Satureja hortensis L., S. montana L., Elsholzia cristata Willd., Hyssopus officinalis L., H. аngustifolius M. Bieb., Origanum vulgare L., Nepeta transcaucasica Grossh., Salvia officinalis L., S. sclarea L. and S. aethiopis L. are ecologically adaptable species with good prospects to be deployed as industrial plants in Ukrainian Polissya. Being extremely perspective, in trodu ced plants can be a valuable source of enriching new plant resources and may be used as base breeding material for comprehensive selection research to create highly adaptive varieties.